Effect of polydiacetylene-based nanosomes on cell viability and endocytosis. (1st April 2019) - Park, Kyu Ha; Ku, Minhee; Yoon, Nara; Hwang, Dae Youn; Lee, Jaebeom; Yang, Jaemoon; Seo, Sungbaek
Abstract: Polydiacetylene-based nanoparticles have been developed as nanocarriers for various bio-applications. However, how nanocarriers enter the cell environment and affect cell viability has not yet been considerably explored. In this study, polydiacetylene-based nanoliposomes (nanosomes) were electrostatically complexed with rhodamine fluorophores. Based on real-time cell imaging and cell viability assessment, the most highly polymerized nanosomes were found to be less toxic to cells. Moreover, it was revealed that the rhodamine/polydiacetylene nanosome complex dissociates at cell environment, the polydiacetylene nanosome penetrates into cells, as suggested by the fluorescence observed in confocal microscopy images.